Job Satisfaction, Work Environment, and Organizational Commitment as Predictors of Turnover Intention among “Richness” Bali Art Instructors - Irawan, Celesta Flora; Widiastini, Ni Made Ary (Amkop Management Accounting Review (AMAR), 2026)
This study aims to examine the effects of job satisfaction, work environment, and organizational commitment on turnover intention among instructors in the “Richness” art community in Bali. Previous studies have predominantly focused on formal organizations, leaving limited attention to turnover intention in non-formal, community-based organizations, particularly within the arts sector. Furthermore, the integration of Job Embeddedness Theory dimensions; fit, links, and sacrifice, within this context remains underexplored. A quantitative approach was employed by involving all active instructors as of February 2026, totaling 36 respondents, using a saturated sampling (census) technique. Data were collected through a Likert-scale questionnaire (1–5) and analyzed using multiple linear regression with SPSS. The findings indicate that job satisfaction, work environment, and organizational commitment each have a negative and significant effect on turnover intention. Simultaneously, these variables also exert a significant influence, with a coefficient of determination (R²) of 0.871, indicating that 87.1% of the variance in turnover intention is explained by the model. The study contributes theoretically by extending the application of Job Embeddedness Theory to nonformal, community based art organizations. Practically, the findings suggest that enhancing job satisfaction, fostering a supportive work environment, and strengthening organizational commitment are essential to reducing turnover intention.